Use of scenedesmus for the removal of nutrients and heavy metals from waste waters of the textile industry - Pérez Silva, Karen Rocío; Vega Bolaños, Asly Michell; Hernández Rodríguez, Luisa Carolina; Parra Ospina, David Alejandro; Ballen Segura, Miguel Ángel (Ingeniería Solidaria, 2016)
Introduction: This article is a derivative research product from the project “Use of waste waters as alternative substrate to generate microalgae biomass”, developed by the Environmental and Bioprocessing Engineering Research Incubator (SIIAB) of the Universidad Sergio Arboleda. The project was implemented during the year 2015. The objective of the research was to evaluate the use microalgae Scenedesmus sp. as a processing tool of industrial waste waters produced in a textile company located in Bogota (Colombia) that presents high concentrations of heavy metals, aluminum and inorganic nutrients, all of which can alter the quality of superficial and subterranean body of waters.Methodology: The research evaluated three different dilutions of waste waters (100 %, 50 % and 20 %) in order to assess the effect the industrial effluent has on the growth of microalgae during a 15-day period.Results: A faster growth of Scenedesmus was obtained in undiluted water (100 % concentration) and in such a way were obtained reductions in aluminum (of 88.8 %), chrome (of 85.21 %), nitrates (of 99.81 %) and nitrites (of 99.9 %), and to a lesser degree in content of organic material (of 25.2 %).Discussion: The microalgae Scenedesmus sp. showed to contribute in phytoremediation on waste waters of the textile industry, which can be used as alternative substrate to generate microalgae biomass.
Keywords: waste waters; metal removal; Scenedesmus; textile